Two TPL-Binding Motifs of ARF2 Are Involved in Repression of Auxin Responses - Choi, Hee-Seung; Seo, Minji; Cho, Hyung-Taeg (Frontiers in Plant Science, 2018)
Auxin signaling is finalized by activator auxin response factors (aARFs) that are released from Auxin/Indole-3-Acetic Acid (Aux/IAA) repressors and directly activate auxin-responsive genes. However, it remains to be answered how repressor ARFs (rARFs) exert their repression function. In this study, we assessed the molecular and biological functions of two putative co-repressor-binding motifs (EAR and RLFGI) of ARF2 (a rARF) in Arabidopsis thaliana. In the yeast two-hybrid assay, the EAR mutation moderately and the RLFGI mutation, or both motifs, almost completely disrupted the interaction between the co-repressor TOPLESS (TPL) and the repressive motifs-containing middle domain (MD) of ARF2. The ARF2-MD interacted not only with TPL but also with TPL homologs (TPRs). Root hair-specific overexpression of rARFs (ARF1–4, 9–11, and 16) considerably inhibited root hair growth, suggesting that rARFs generally function as repressors in the auxin-responsive root hair single cell. Individual mutation of the ARF2 EAR or RLFGI motif slightly and both mutations greatly compromised ARF2-mediated inhibition of root hair growth and auxin-responsive gene expression. In addition, flowering time and seed size, two representative arf2 mutant phenotypes, were examined to assess the function of the repressive motifs in mutant-complementation experiments. ARF2-mediated inhibition of flowering and seed growth was suppressed considerably by the individual mutation of EAR or RLFGI and almost completely by both mutations. These results suggest that EAR and RLFGI work together as major repressive motifs for ARF2 to recruit TPL/TPR co-repressors and to exhibit its repressive biological functions.